\int\limits_{b}^{a}f^\prime(x) dx = f(a) - f(b)
\pi = \int\limits_{-1}^{1}\frac{dx}{\sqrt{1-x^2}}
e = \lim_{n\to\infty}\sum_{x=0}^n\frac{1}{x!}
\phi = 2\sin\frac{3\pi}{10}
\gamma = \lim_{n\to\infty}(-\ln n+\sum_{x=1}^n\frac{1}{x})
\Alpha\alpha\ \Beta\beta\ \Gamma\gamma\ \Delta\delta\ \Epsilon\epsilon\ \Zeta\zeta\ \Eta\eta\ \Theta\theta\ \Iota\iota\ \Kappa\kappa\ \Lambda\lambda\ \Mu\mu\ \Nu\nu\ \Xi\xi\ \Omicron\omicron\ \Pi\pi\ \Rho\rho\ \Sigma\sigma\ \Tau\tau\ \Upsilon\upsilon\ \Phi\phi\ \Chi\chi\ \Psi\psi\ \Omega\omega

<math>\int\limits_{b}^{a}f^\prime(x) dx = f(a) - f(b)</math><br />
<math>\pi = \int\limits_{-1}^{1}\frac{dx}{\sqrt{1-x^2}}</math><br />
<math>e = \lim_{n\to\infty}\sum_{x=0}^n\frac{1}{x!}</math><br />
<math>\phi = 2\sin\frac{3\pi}{10}</math><br />
<math>\gamma = \lim_{n\to\infty}(-\ln n+\sum_{x=1}^n\frac{1}{x})</math><br>
<math>\Alpha\alpha\ \Beta\beta\ \Gamma\gamma\ \Delta\delta\ \Epsilon\epsilon\ \Zeta\zeta\ \Eta\eta\ \Theta\theta\ \Iota\iota\ \Kappa\kappa\ \Lambda\lambda\ \Mu\mu\ \Nu\nu\ \Xi\xi\ \Omicron\omicron\ \Pi\pi\ \Rho\rho\ \Sigma\sigma\ \Tau\tau\ \Upsilon\upsilon\ \Phi\phi\ \Chi\chi\ \Psi\psi\ \Omega\omega</math>

Darth Disco (talk) 18:14, May 15, 2016 (UTC)

Ad blocker interference detected!

Wikia is a free-to-use site that makes money from advertising. We have a modified experience for viewers using ad blockers

Wikia is not accessible if you’ve made further modifications. Remove the custom ad blocker rule(s) and the page will load as expected.